Direct and indirect effects of management and landscape on biological pest control and crop pest infestation in apple orchards. Issue 1 (7th November 2022) - Daelemans, Robin; Hulsmans, Eva; Laenen, Emily; Remy, Serge; Beliën, Tim; Honnay, Olivier
Abstract: Biological pest control, relying on naturally occurring predator–prey dynamics, is considered a key element to achieve more sustainable farming systems. However, the combined effects of local management and landscape factors on communities of natural enemies as well as the cascading effects on pest infestations are rarely addressed, especially in perennial crops. Here, we used Piecewise Structural Equation Modelling (PSEM) to test direct and indirect effects of landscape composition, landscape configuration and local management practices on natural enemy communities, the pest control services they provide and ultimately on pest infestation and pest‐related yield damage in apple crops. To this end, we surveyed 12 organic and 12 Integrated Pest Management (IPM) orchards during three consecutive years, and we also established a semi‐natural benchmark to quantify the extent to which predator communities in the orchards were degraded. Natural enemies had a different community composition and were more abundant in organic orchards compared with IPM orchards. This had a small and positive effect on sentinel egg predation rates in organic orchards, but overall had very little impact on actual apple pest infestation. On the contrary, apple pest infestation levels were directly and positively affected by organic management practices and by increasing semi‐natural habitat cover and landscape edge density. Compared with a semi‐natural benchmark, both agricultural management systems showed degraded predator communities, which translated into an impaired delivery of biological control services. Synthesis and applications. Our results indicate that organic management and habitat conservation can enhance natural enemies and stimulate pest control, but also show that these factors can enhance pest infestations and can even lead to an overall increase in pest‐related crop damage. Our study thus highlights the complex interplay of ecosystem services and disservices provided by biodiversity, which should be taken into account when advising farmers, policy makers and land managers on effective and sustainable strategies to control pest species and safeguard crop production. Abstract : Our results indicate that organic management and habitat conservation can enhance natural enemies and stimulate pest control, but also show that these factors can enhance pest infestations and can even lead to an overall increase in pest‐related crop damage. Our study thus highlights the complex interplay of ecosystem services and disservices provided by biodiversity, which should be taken into account when advising farmers, policy makers and land managers on effective and sustainable strategies to control pest species and safeguard crop production.